An acceptable time - L'Engle, Madeleine (490 Time quintet, 2007)
Polly's stay with her grandparents in Connecticut becomes an extraordinary experience as she encounters old friends and mysterious strangers and finds herself traveling back in time to play a crucial role in a prehistoric confrontation.